2012
DOI: 10.1103/physrevb.86.085437
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional quantum channel in a graphene line defect

Abstract: Using a tight-binding model, we study a line defect in graphene where a bulk energy gap is opened by sublattice symmetry breaking. It is found that sublattice symmetry breaking may induce many configurations that correspond to different band spectra. In particular, a gapless state is observed for a configuration which hold a mirror symmetry with respect to the line defect. We find that this gapless state originates from the line defect and is independent of the width of the graphene ribbon, the location of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 73 publications
0
41
0
1
Order By: Relevance
“…The superlattices with adjacent AB and BA stacking orders, with boundaries that may support ZLMs, can also be realized in graphene on top of h-BN substrates as a result of lattice mismatch [315]. In addition to the line defect exhibited when the stacking order of bilayer graphene changes, 1D ZLMs can also appear along the line defect of monolayer graphene if a suitable staggered sublattice potential is present [316].…”
Section: Proposals and Electronic Structuresmentioning
confidence: 99%
“…The superlattices with adjacent AB and BA stacking orders, with boundaries that may support ZLMs, can also be realized in graphene on top of h-BN substrates as a result of lattice mismatch [315]. In addition to the line defect exhibited when the stacking order of bilayer graphene changes, 1D ZLMs can also appear along the line defect of monolayer graphene if a suitable staggered sublattice potential is present [316].…”
Section: Proposals and Electronic Structuresmentioning
confidence: 99%
“…2 Electronic and magnetic properties of ribbons with octagon-pentagon line defects are now being intensively investigated. [19][20][21][22] In this work we study the appearance of localized states in graphene-based systems with octagonal defects. We investigate octagonal defect lines appearing both in graphene ribbons and in carbon nanotubes, which can be considered as rolled-up ribbons.…”
Section: Introductionmentioning
confidence: 99%
“…The first one, (2,0), consists of domains with the aligned crystallographic orientations θ L = θ R = θ = 0 • (d ≈ 0.5 nm) and separated by a zigzag-oriented interface of one octagon and two side-sharing pentagons. [16][17][18][19]23 The repeat vector (2,1) of the second one implies θ L = θ R = θ = 10.9 • (d ≈ 0.65 nm) and its interface region includes pentagon-heptagon pairs. 6,17 We would like to note that while we study two representative GBs, (2,0) and (2,1) (corresponding to aligned and misaligned crystallographic orientations), we believe that our findings are generic and remain valid for other GBs in graphene.…”
Section: Basicsmentioning
confidence: 99%
“…[12][13][14][15] This provides a strong motivation for investigation of morphological, electronic, and spin properties of GBs. A number of studies have been recently reported addressing the band structure, [16][17][18][19][20] spin polarization, 16,17,21,22 electron transport and scattering 12,13,20 in GBs. However, all these studies were limited to the case of electrically neutral graphene, and very little is presently known on how the electronic and transport properties of GBs are modified at nonzero electron densities (i.e., away from the Dirac point).…”
Section: Introductionmentioning
confidence: 99%